2012
DOI: 10.4314/bcse.v27i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of thermally stable metal substituted hydroxy apatites for the selective oxidation of light paraffins

Abstract: ABSTRACT. Hydroxyapatite and a series of hydroxyapatite-type compounds containing Co, Fe or Sr were synthesized by co-precipitation and characterized by ICP-OES, BET, IR, Raman spectroscopy, powder and in-situ XRD, SEM, TEM, TPR, TPD and TGA. In-situ XRD and TGA studies indicate that the materials are able to maintain their structure at temperatures reaching 900 °C. The TPD data indicated that acidic sites of varying strengths were present in all the three hydroxyapatites. From SEM, the surface of the material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The additional mass loss was due to the removal of all the organic compounds present in the core of the sample. A similar profile was observed in Singh and Jonnalagadda's work . However, the hydroxyapatite prepared was synthetic (i.e.…”
Section: Resultssupporting
confidence: 84%
“…The additional mass loss was due to the removal of all the organic compounds present in the core of the sample. A similar profile was observed in Singh and Jonnalagadda's work . However, the hydroxyapatite prepared was synthetic (i.e.…”
Section: Resultssupporting
confidence: 84%
“…Rare earth elements have the characteristics of unoccupied 4f orbitals and lanthanide contraction, which result in their applicability as catalysts or catalytic components. [44][45][46] We also reported the advantages of using rare earth-loaded mixed oxide catalysts in value-added conversions. 34 38,39 Triazole-containing organics possess anti-microbial, antimalarial, anti-tumor, anti-tubercular, anti-inammatory, and anti-convulsant properties.…”
Section: Introductionmentioning
confidence: 97%
“…The above applications highlight the importance of a facile synthetic route for triazoles to surmount the hindrances such as elaborate reaction conditions, high temperature maintenance, long work-up procedures and low yields. In the earlier studies, we have reported the synthesis and characterization of diverse metal (Fe Co, Pt, Sr, Ir, and V) substituted hydroxyapatites and their scope as heterogeneous catalysts in value-added organic transformations such as selective oxidation of n-pentanes and in Knoevenagel condensation reactions with excellent yields [47,48,49,50]. We have also reported the scope of Sm(III) based coordination polymer as a viable yellow light emitter [51].…”
Section: Introductionmentioning
confidence: 99%